Parentalidade e conjugalidade: a experiência de mulheres que tiveram um filho vítima de incesto - Melo, Liliane Maria Martins de Barros (2008)
This study is focused on trying to understand the experience of parenthood and conjugality lived by some women/mothers who have had their own men and kids involved in incestuous relations. The methodology used here was the qualitative one. To collect the information/data needed, it was created a scrapbook . This photography album was developed in order to help introduce the sexual abuse issue to the women who have agreed to talk about and share this family drama they have all been through. Attempting to approach whatever subjects that could be possibly related to the purposes of this work, it was also added a semi-guided interview. We tried to observe the various ways these women/mothers react whenever having their children sexually abused by their own men, as well as the kind of relationship they keep with these men/aggressors. The results go to show that there is an ideal concept of family: dad, mom and kids living altogether. This ideal concept, however, is left behind as soon as the incestuous abuse situations are revealed. We were able to confirm that domestic violence is also a very important part of this whole perversion process (and when it comes to conjugal relationships, it can be expressed in many different ways, such as: physical aggressions, economic subordination or even possessive jealousy). Conjugality is commonly idealized as a relation of affection, companionship and respect. But this kind of perception changes as the incestuous abuse cases are uncovered. Inside the the parenthood experience itself, our analysis could verify that there are genuine love bonds between these moms and their children. These love bonds, inevitably, tend to become more fragile (or even break) as a result of whatever new circumstances that might appear once the incestuous perversion is revealed. All women interviewed here expressed the practice of parenthood as an affection relation, which seemed to be strong enough to overcome each and every adversity they have experienced. To these women, motherhood itself represents a very important basis used to consolidate their own identities. We understand that this work is relevant to help emphasize our society needs in terms of public administration and management. We also expect this study can contribute to stimulate the institutions and centers which support victims of sexual abuse to offer some sort of aid to all those who have been involved in situations of incestuous perversion (including the women and mothers who decide to denounce their men, once this being done, they are the ones who have their lives entirely changed emotionally, affectively and economically speaking)